Information Technology for Manufacturing: Reducing Costs and Expanding Capabilities - Ake, Kevin (CRC Press, 2009)
The rate of change in manufacturing today is faster than ever. Retailers and consumers demand flexibility and responsiveness, regulatory oversight is on the rise, and increasing consolidations require companies to demonstrate cost and efficiency improvements.